The Mediating Effect of Managerial Competencies in the Relationship between Corporate Governance and Financial Performance of Companies in Uganda: A Multi-Theoretic Approach - Rwakihembo, John; Oceng, Peter; Kule, John Baguma; Kamukama, Nixon; Kijjambu, Nsambu Fredrick (Journal of Strategic Management, 2024)
Purpose: The dwindling financial performance of companies has attracted enormous attention globally for many years, and corporate governance remains a matter of public and academic debate. This study aimed to establish the mediating role of managerial competencies in the relationship between corporate governance and the financial performance of companies in Uganda. Materials and Methods: The study applied a positivist paradigm and a cross-sectional design. Data were obtained from a sample of 394 private companies drawn from central and western Uganda. Companies were stratified by region, sectors, and subsectors; and then selected using simple random sampling from each stratum. A structured questionnaire was distributed to board members, Chief Executive Officers, accountants, Internal Auditors, and managers who were selected purposively. Principle Component Analysis and varimax rotation were employed for data extraction and reduction. The hierarchical regression technique was employed for data analysis. Findings: The study results confirmed managerial competencies to be a partial mediator, of the relationship between corporate governance and financial performance of companies in Uganda. Implications to Theory, Practice and Policy: Building on a multi-theoretical approach, the study advocates for the revision of corporate governance and recommends private companies prioritize managerial competencies in their recruitment processes and training programs to enhance their financial performance.